Evolución de la paridad del poder adquisitivo y el efecto del producto interno bruto, la inversión extranjera y el precio del petróleo 2013-2022 (2023)
An important fact in Colombia's economy is the significant process of improving purchasing power parity so far in the 21st century. Taking the hypothesis of relative purchasing power parity as the relationship between the foreign price level over the domestic price level of a basket of goods through the exchange rate, it is evident that the real exchange rate index is used to measure this hypothesis of purchasing power parity and that for Colombia purchasing power has deteriorated compared to its trading partners. In real terms, Colombia's price level is higher compared to other countries, resulting in a higher cost of living for its inhabitants.